Les erreurs de déterminants chez les étudiants en français langue étrangère: une perspective microtextuelle - Jespersen, Janine (Studia Romanica Posnaniensia, 2007)
The goal of this paper is to provide teachers of French with the origin of main errors made by Slavic students in the use of articles. In the languages of these students tjjere are no articles. Of particular interest are binominal structures, for example: text analysis, (l’analyse de texte) vs analysis of the text, (l’analyse du texte). In the first example an entity is subcategorised as a generic entity; in the second example this expression is used as the noun of a process: the text was read, discussed, explored .........The analysis of the te x t............. Constructions of this type are often used in order to provide summaries and introduce abstractions in scientific and academic texts. I shall apply the theory of Alain Berrendonner to these structures and I shall suggest some ways of correcting errors in this area.